2012
DOI: 10.3109/10826084.2012.726311
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Episodic Drinking in College Females: An Exploration of Expectancies, Consequences, and Self-Efficacy

Abstract: Differences on expectancies and self-efficacy between college females who engage in heavy episodic drinking (HED) and non-HED were examined. Students (N = 95) from Southern California filled out the Comprehensive Effects of Alcohol, Cognitive Appraisal of Risky Events, and Drinking Context Convivial Drinking scales as well as self-efficacy, alcohol use, and demographic items in the fall semester of 2008. Logistic and linear regression showed that greater positive expectancies and lower self-efficacy were predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…In addition, two studies assessed the association between expectancies and self-efficacy of PBS use, but these investigations produced mixed results. Lienemann and Lamb (2013) found that stronger positive expectancies were associated with lower perceived ability to engage in protective behaviors in drinking situations (e.g., using condoms during sex while under the influence of alcohol) whereas Kraus and colleagues (2012) found no such support.…”
Section: Pbs and Expectanciesmentioning
confidence: 98%
“…In addition, two studies assessed the association between expectancies and self-efficacy of PBS use, but these investigations produced mixed results. Lienemann and Lamb (2013) found that stronger positive expectancies were associated with lower perceived ability to engage in protective behaviors in drinking situations (e.g., using condoms during sex while under the influence of alcohol) whereas Kraus and colleagues (2012) found no such support.…”
Section: Pbs and Expectanciesmentioning
confidence: 98%
“…While results of the expectancy-alcohol use relationship have been mixed across domains (e.g., prevention and treatment of abuse and dependence, prediction of future consumption), it can be stated with confidence that positive alcohol-related expectancies better predict alcohol consumption and tend to result in poorer treatment outcomes (Jones et al, 2001). Research has supported this line of thought, demonstrating that positive alcohol-related expectancies are associated with problematic drinking (Armeli, Todd, & Mohr, 2005;Lienemann & Lamb, 2013;Monk & Heim, 2013;Nicolai et al, 2012). Moreover, both alcohol-related expectancies and affect regulation strategies (e.g., drinking to cope with negative affect) can serve as predictive measures in distinguishing problem or heavy drinkers from social or light drinkers (Houben & Wiers, 2008;Marlatt & Gordon, 1985;Martens et al, 2008).…”
Section: Affective and Cognitive Conceptualizations Of Problem Drinkingmentioning
confidence: 99%